Pengaruh Celebrity Endorsment (Bintang Iklan), Electronic Word Of Mouth (E-Wom) Dan Brand Image (Citra Merek) Terhadap Purchase Decision (Keputusan Pembelian) Produk After Beaute Pada PT Mega Irianto Indonesia Di Bandar Lampung - Deni Alvianingsih; Yateno; Selamet Fuadi (Jurnal Manajemen DIVERSIFIKASI, 2025)
To determine whether celebrity endorsement affects the purchase decision. To determine whether electronic word of mouth (e-wom) affects the purchase decision. To determine whether the brand image affects the purchase decision. To find out whether celebrity endorsement, electronic word of mouth (e-wom), and brand image influence the purchase decision. The sample of this study is consumers After Beaute amounting to 100 respondents. Data collection using questionnaires and literature studies. Data analysis using prerequisite testing instruments, namely validity test and reliability test. Prerequisite test analysis using normality test and linearity test. Hypothesis test using multiple linear regression analysis, Partial Test (t Test), Test together (F test) and test coefficient of determination (R2) using the program (SPSS). The research results show that 1). Celebrity endorsement has not effect on purchase decisions. 2). Electronic word of mouth (e-wom) has not effect on purchase decisions. 3). Brand image has a significant influence on purchase decisions.